Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T15:26:37+01:00
A)
(x+4)-(3-2x)=(3x+4)-(6+x)
x+4-3+2x=3x+4-6-x
4-3-4+6=3x-x-2x-x
3=-x
x=-3

b)
-3(x+2)-2(x+3)=-7
-3x-6-2x-6=-7
-x-12=-7
-x=-7+12
-x=5
x=5

c)
4(2x-8)-6(x-4)=2
8x-32-6x+24=2
2x=2+32-24
2x=10/:2
x=5

d)
3(2x-1)-6(x-3)=4(4-x)
6x-3-6x+18=16-4x
18-3=16-4x
4x=16-15
4x=1
x=1/4

e)
-5(2x-1)+4(x-6)=3(5-x)

-10x+5+4x-24=15-3x
-6x-19=15-3x
-6x+3x=15+19
-3x=34/-3
x=- 34/3
x= -11 1/3
1 1 1
2010-02-28T15:39:03+01:00
A) (x+4)-(3-2x)=(3x+4)-(6+x)
x+4-3+2x=3x+4-6-x
3x+1=2x-2
3x-2x=-2-1
x=-3

b) -3(x+2)-2(x+3)=-7
-3x-6-2x-6=-7
-5x-12=-7
-5x=-7+12
-5x=5 /:(-5)
x=-1

c) 4(2x-8)-6(x-4)=2
8x-32-6x+24=2
2x-8=2
2x=2+8
2x=10 / :2
x=5

d) 3(2x-1)-6(x-3)=4(4-x)
6x-3-6x+18=16-4x
15=16-4x
4x=16-15
4x=1 / :4
x=¼

e) -5(2x-1)+4(x-6)=3(5-x)
-10x+5+4x-24=15-3x
-6x-19=15-3x
-6x+3x=15+19
3x=34 / :3
x=11⅓